Uterine teratoma and the role of short-tandem repeat genotyping in understanding origins - Abdelrahman AlAshqar; Vijaya Kadam Maruthi; Rita Abi-Raad; Michelle Greenman; Pei Hui; Elena Ratner; Gary Altwerger; Alessandro Santin; Vaagn Andikyan (Gynecologic Oncology Reports)
Background: Uterine teratomas are a rare entity with a debated origin. Given its rarity and limitations of diagnostic imaging, diagnosis is typically determined pathologically following surgical resection based on the presence of tissue derived from all germ cell layers. Unlike its ovarian counterpart, the developmental origins are poorly understood; however, recently introduced molecular testing has revolutionized our understanding of these rare tumors. Case: A 44-year-old primiparous woman presented with a four-week history of vaginal bleeding attributed to the presence of a uterine mass. Given the inconclusive results of imaging and endometrial sampling, the patient opted for a total hysterectomy and was diagnosed with a mature cystic uterine teratoma. Short-tandem repeat genotyping performed on the teratoma and fallopian tube tissues confirmed genetic similarity apart from loss of heterozygosity in six of 16 loci. Conclusion: This case demonstrates a mature uterine teratoma potentially arising from host pluripotent stem cells supported by molecular testing. The presence of a diploid karyotype and genetic similarity with the host tissues rule out the possibility of a nonfertilized ovum and residual fetal tissue as the origins, respectively, refuting the blastomere and perhaps the parthenogenetic hypotheses. Future work should utilize advanced molecular testing and investigate the role of pluripotent stem cells in the uterus to enhance our understanding of the origins of these rare tumors.